2019
DOI: 10.1038/s41433-019-0494-z
|View full text |Cite
|
Sign up to set email alerts
|

New anti-hyperglycaemic agents for type 2 diabetes and their effects on diabetic retinopathy

Abstract: There has been an increase in the range of non-insulin anti-hyperglycaemic agents used to treat type 2 diabetes. With the globally rising rates of type 2 diabetes and complications such as diabetic retinopathy, it is important for ophthalmologists to be aware of these new agents and their impacts on diabetic retinopathy and diabetic macular oedema. We conducted a review of the literature to determine if there were any beneficial or harmful effects of the currently used anti-hyperglycaemic agents on diabetic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 72 publications
1
26
0
Order By: Relevance
“…A recent study reported that the elevated risk of retinopathy was largely dependent on the baseline presence of pre-existing retinopathy, and that the occurrence of retinopathy primarily resulted from the magnitude and rapidity of glycemic reduction [27]. Furthermore, several previous studies reported no association between GLP-1R agonists and diabetic retinopathy [28][29][30], which is in agreement with the results of the current study.…”
Section: Discussionsupporting
confidence: 92%
“…A recent study reported that the elevated risk of retinopathy was largely dependent on the baseline presence of pre-existing retinopathy, and that the occurrence of retinopathy primarily resulted from the magnitude and rapidity of glycemic reduction [27]. Furthermore, several previous studies reported no association between GLP-1R agonists and diabetic retinopathy [28][29][30], which is in agreement with the results of the current study.…”
Section: Discussionsupporting
confidence: 92%
“…Diabetic retinopathy is one of the most common microvascular complications of diabetes mellitus. The main features of diabetic retinopathy are the occlusion and retinal hard exudates of retinal microvessels, which lead to blindness in severe cases [ 1 ]. Metabolic abnormalities caused by persistent hyperglycemia is the main pathogenesis of diabetic retinopathy, which can damage retinal microvascular system, including changes of capillary permeability, destruction of blood-retinal barrier, retinal leakage, macular edema, retinal vitreous hemorrhage, neovascularization, and retinal detachment [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…The detection . Given the global increase in the incidence of type 2 diabetes and complications such as DR, ophthalmologists need to know about these new agents and their effect on diabetic retinopathy and diabetic macular oedema, according to a multicenter study in Australia [40].…”
Section: Dr Treatment Issuesmentioning
confidence: 99%